Study on Increasing the Cracking Resistance of Unsaturated Polyester Composites with MMA and Rice Husk Fiber Reinforcement - Nusyirwan Nusyirwan; Rully Pratama (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2023)
The development of polymer composite materials has been widely developed as an alternative material to replace metal materials due to various advantages such as having relatively good mechanical strength, low density, and easy manufacturing process, but polymers have many disadvantages that they easily crack when impacted. One of the most widely used materials for composite matrices is unsaturated polyester polymers which are widely used in vehicle, aircraft, and ship hull components as well as vehicle components. The crack study is important because it causes the material to no longer be able to support loads below its yield strength, therefore causing failure to occur more quickly. One way to overcome material failure due to cracks in composite materials is to prevent crack propagation by adding reinforcing materials. In this study, a composite material was made using rice husk fiber to increase the crack resistance of the polyester composite matrix. From the results of the crack test, it is known that there is a tendency to increase the percentage variable of the addition of rice husk by 5%, 10%, 15%, and 20%. The expected value obtained to determine the crack resistance of the material is the value of the stress intensity factor (K1c). The highest K1c price was obtained at a 15% rice husk percentage variable of 1.558 MPa.m0.5, this price could increase the price of the pure polyester stress intensity factor (K1c) by 0.667 MPa.m0.5, indicating an increase of 233.58%.